Two-Way Satellite-HAP-Terrestrial Networks With Non-Orthogonal Multiple Access - Guo, Kefeng; Shuai, Haifeng; Li, Xingwang; Yang, Liang; Tsiftsis, Theodoros A.; Nallanathan, Arumugam; Wu, Min (IEEE transactions on vehicular technology, 2024)
Satellite-high altitude platform (HAP)-terrestrial networks have been considered as an indispensable infrastructure of next-generation networks because they can offer massive access service with high throughput and broad coverage connections. Meanwhile, non-orthogonal multiple access (NOMA) and two-way relaying techniques are considered as potential technologies to enhance the spectrum efficiency and connectivity. Thus, in this article, the performance of two-way satellite-HAP-terrestrial networks with NOMA, which are subject to imperfect channel state information and successive interference cancellation, is investigated. Closed-form and asymptotic expressions for the outage probability, and ergodic capacity are derived to verify the impact of the system and channel parameters on the considered network. Simulation results indicate that the optimization power allocation factor is independent of the channel fading.